Preparation and characterisation of poly(vinyl) alcohol (PVA)/starch (ST)/halloysite nanotube (HNT) nanocomposite films as renewable materials - Abdullah, Zainab; Dong, Yu (Springer, 2018)
Poly(vinyl) alcohol (PVA)/starch (ST) films (weight ratio: 80/20) were prepared using a solution casting method, in the presence of 30 wt% glycerol (GL) as a plasticiser. Halloysite nanotubes (HNTs) were used as relatively new clay nanofillers to PVA/ST/GL blends for more economical material packaging. HNTs at filler loadings of 0.25, 0.5, 1, 3 and 5 wt% were incorporated to enhance mechanical and thermal properties of resulting PVA/ST/HNT nanocomposites. The tensile strength of such nanocomposites was found to be improved by 20 and 3.4%, respectively, with the inclusion of 0.25 and 0.5 wt% HNTs as opposed to those of PVA/ST/GL blends. However, a decreasing strength trend was observed beyond the HNT loading of 0.5 wt% due to HNT agglomeration, as evidenced by relevant micrographs via scanning electron microscopy (SEM). However, Young’s modulus was enhanced by 148% with the addition of 1 wt% HNTs when compared with PVA/ST/GL blends. X-ray diffraction (XRD) analysis is indicative of slightly intercalated nanocomposite structures formed at low HNT loadings of 0.25–1 wt%. In general, the incorporation of HNTs improved the thermal stability of PVA/ST/GL blends by increasing melting and decomposition temperatures along with the reduction in weight loss.